Host-Induced Gene Silencing of MoAP1 Confers Broad-Spectrum Resistance to Magnaporthe oryzae - Guo, Xiao-Yi; Li, Yan; Fan, Jing; Xiong, Hong; Xu, Fu-Xian; Shi, Jun; Shi, Yi; Zhao, Ji-Qun; Wang, Yi-Fu; Cao, Xiao-Long; Wang, Wen-Ming (Frontiers in Plant Science, 2019)
Rice blast caused by Magnaporthe oryzae (M. oryzae) is a major threat to global rice production. In recent years, small interference RNAs (siRNAs) and host-induced gene silencing (HIGS) has been shown to be new strategies for the development of transgenic plants to control fungal diseases and proved a useful tool to study gene function in pathogens. We here tested whether in vitro feeding artificial siRNAs (asiRNAs) could compromise M. oryzae virulence and in vivo HIGS technique could improve rice blast resistance. Our data revealed that silencing of M. oryzae MoAP1 by feeding asiRNAs targeting MoAP1 (i.e., asiR1245, asiR1362, and asiR1115) resulted in inhibited fungal growth, abnormal spores, and decreased pathogenicity. Among the asiRNAs, asiR1115 was the most inhibitory toward the rice blast fungus. Conversely, the asiRNAs targeting three other genes (i.e., MoSSADH, MoACT, and MoSOM1) had no effect on fungal growth. Transgenic rice plants expressing RNA hairpins targeting MoAP1 exhibited improved resistance to 11 tested M. oryzae strains. Confocal microscopy also revealed profoundly restricted appressoria and mycelia in rice blast-infected transgenic rice plants. Our results demonstrate that in vitro asiRNA and in vivo HIGS were useful protection approaches that may be valuable to enhance rice blast resistance.